(3GdEOGQI GdESJQGJjLjIs - (3RjO efjQ(B, (3YHhjs ((3YeGf(B:s (3OGQ cfhR GdeYQaI ddfTQ hGdJhRjY(B,s, 2006)
(3fTCI GdEOGQI GdESJQGJjLjI hJWhQgG(B- (3eaGgje GdEOGQI GdESJQGJjLjI(B- (3GdEOGQI GdESJQGJjLjI aj GdbWGY GdYGe(B- (3YedjGJ GdEOGQI GdESJQGJjLjI(B- (3GdJNWjW GdESJQGJjLj(B- (3GdEOGQI GdESJQGJjLjI aj GdJfejI GdEOGQjI(B- (3CfeGW GdEOGQI GdESJQGJjLjI hGdEHOGYjI(B- (3JMhjd GdESJQGJjLjI ef GdYdhe GdYScQjI Gdi YUQ GdYhdeI(B- (3QDjI GSJQGJjLjI ddhdGjGJ GdeJMOI hGSJQGJjLjI GdEMJhGA GdLOjOI(B- (3GdWjQGf GdeOfj aj OHj eQcR eJWhQ dHfGA aQb GdYed(B.s
(3GdeQGLY U(B. 173s
Keywords: (3GdEOGQIs; (3GdEOGQI GdESJQGJjLjIs